A multivalent Kaposi sarcoma-associated herpesvirus-like particle vaccine capable of eliciting high titers of neutralizing antibodies in immunized rabbits. Issue 30 (9th July 2019) - Mulama, David H.; Mutsvunguma, Lorraine Z.; Totonchy, Jennifer; Ye, Peng; Foley, Joslyn; Escalante, Gabriela M.; Rodriguez, Esther; Nabiee, Ramina; Muniraju, Murali; Wussow, Felix; Barasa, Anne K.; Ogembo, Javier Gordon
Highlights: The first KSHV-LPs incorporating four glycoprotein mediating virus infection. KSHV-LPs elicited robust KSHV glycoproteins-specific antibodies response in immunized rabbits. Purified rabbit KSHV glycoprotein-specific IgGs blocked KSHV infection in diverse cell types. Abstract: Kaposi sarcoma-associated herpesvirus (KSHV) is an emerging pathogen and the causative agent of multiple cancers in immunocompromised patients. To date, there is no licensed prophylactic KSHV vaccine. In this study, we generated a novel subunit vaccine that incorporates four key KSHV envelope glycoproteins required for viral entry in diverse cell types (gpK8.1, gB, and gH/gL) into a single multivalent KSHV-like particle (KSHV-LP). Purified KSHV-LPs were similar in size, shape, and morphology to KSHV virions. Vaccination of rabbits with adjuvanted KSHV-LPs generated strong glycoprotein-specific antibody responses, and purified immunoglobulins from KSHV-LP-immunized rabbits neutralized KSHV infection in epithelial, endothelial, fibroblast, and B cell lines (60–90% at the highest concentration tested). These findings suggest that KSHV-LPs may be an ideal platform for developing a safe and effective prophylactic KSHV vaccine. We envision performing future studies in animal models that are susceptible to KSHV infection, to determine correlates of immune protection in vivo .